Endogenous Digitalis-Like Factors: An Overview of the History - Buckalew, Vardaman M. (Frontiers in Endocrinology, 2015)
The sodium pump is a ubiquitous cell surface enzyme, a Na, K ATPase, which maintains ion gradients between cells and the extracellular fluid (ECF). The extracellular domain of this enzyme contains a highly conserved binding site, a receptor for a plant derived family of compounds, the digitalis glycosides. These compounds inhibit the enzyme and are used in the treatment of congestive heart failure, and certain cardiac arrhythmias. The highly conserved nature of this enzyme and its digitalis receptor led to early suggestions that endogenous regulators might exist. Recent examination of this hypothesis emerged from research in two separate areas: the regulation of ECF volume by a natriuretic hormone (NH), and the regulation of peripheral vascular resistance by a circulating inhibitor of vascular Na, K ATPase. These two areas merged with the hypothesis that NH and the vascular Na, K ATPase inhibitor were in fact the same entity, and that it played a causative role in the pathophysiology of certain types of hypertension. The possibility that multiple endogenous digitalis-like factors (EDLFs) exist emerged from efforts to characterize the circulating enzyme inhibitory activity. In this review, the development of this field from its beginnings is traced, the current status of the structure of EDLFs is briefly discussed, and areas for future development are suggested. Key Words: natriuretic hormone, digitalis-like factor, hypertension, Na, K ATPase, ouabain, marinobufagenin, bufodienolides, cardenolides